Targeting ASCT2-mediated glutamine uptake blocks prostate cancer growth and tumour development - Wang, Qian; Hardie, Rae-Anne; Hoy, Andrew J; van Geldermalsen, Michelle; Gao, Dadi; Fazli, Ladan; Sadowski, Martin C; Balaban, Seher; Schreuder, Mark; Nagarajah, Rajini; Wong, Justin J-L; Metierre, Cynthia; et al. (The Journal of pathology, 2015)
Glutamine is conditionally essential in cancer cells, being utilized as a carbon and nitrogen source for macromolecule production, as well as for anaplerotic reactions fuelling the tricarboxylic acid (TCA) cycle. In this study, we demonstrated that the glutamine transporter ASCT2 (SLC1A5) is highly expressed in prostate cancer patient samples. Using LNCaP and PC‐3 prostate cancer cell lines, we showed that chemical or shRNA‐mediated inhibition of ASCT2 function in vitro decreases glutamine uptake, cell cycle progression through E2F transcription factors, mTORC1 pathway activation and cell growth. Chemical inhibition also reduces basal oxygen consumption and fatty acid synthesis, showing that downstream metabolic function is reliant on ASCT2‐mediated glutamine uptake. Furthermore, shRNA knockdown of ASCT2 in PC‐3 cell xenografts significantly inhibits tumour growth and metastasis in vivo, associated with the down‐regulation of E2F cell cycle pathway proteins. In conclusion, ASCT2‐mediated glutamine uptake is essential for multiple pathways regulating the cell cycle and cell growth, and is therefore a putative therapeutic target in prostate cancer. © 2015 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.